(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
This article analyzes the role and importance of digital educational tools in developing reading literacy. It highlights the potential of e-textbooks, video lessons, audiobooks, interactive platforms, and multimodal texts in fostering students’ abilities to search, analyze, evaluate, and apply information in real-life contexts. The methodological aspects of developing reading literacy in a digital environment are also discussed in accordance with the requirements of international assessment programs such as PISA and PIRLS.